Anti-flash-point anti-glare glass and preparation method thereof
By setting an anti-flash point structure layer on the base layer of the anti-glare glass, the flash point problem on the high-pixel density OLED screen is solved, and the anti-glare effect and visual comfort are achieved.
Patent Information
- Application Number
- CN202510595809.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-09
- Publication Date
- 2025-08-22
AI Technical Summary
The existing anti-glare glass has flash point problems on high-pixel density OLED screens, affecting the display effect and visual experience.
A flash-resistant structure layer is provided on the base layer of the anti-glare glass, and multiple periodic, quasi-periodic or non-periodic holes or protrusions are used to form a flash-resistant structure layer in combination with specific process steps such as coating, coating photoresist, exposure, development, film layer etching, etc.
Effectively reduce the screen flash point, improve the visual experience, and ensure that the anti-glare function is not affected.
Smart Images

Figure CN120518322A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of OLED display devices, and in particular relates to an anti-flash point anti-glare glass and a preparation method thereof. Background Art
[0002] In the process of implementing the present invention, the inventors discovered that the prior art has at least the following problems:
[0003] With the development of technology, flat panel displays have been widely used in various industries. Many applications are in bright light environments, such as outdoor sunlight, indoor lights, etc. Under such conditions, the glass cover of the flat panel display will reflect the ambient light, forming bright spots or reflections on the display screen, which is very detrimental to the user's viewing of the displayed content. The emergence of anti-glare AG glass reduces the intensity of mirror-reflected light and reduces the clarity of the reflection, thereby playing an anti-glare role. However, with the increase in the pixel density of OLED flat panels, adverse factors caused by the AG glass structure, such as flash points, have become a thorny problem. The generation of flash points is due to the refraction, scattering and diffraction of the AG glass structure, which makes the light emitted by the OLED appear uneven in intensity in the human eye, making the viewer feel uncomfortable and seriously affecting the visual experience. When existing anti-glare glass is applied to high-pixel-density OLED screens, there is a flash point problem, which seriously affects the display effect.
[0004] CN110615622A - A method for preparing smooth AG glass and smooth AG glass, discloses a smooth AG glass and a method for preparing the same, wherein the method for preparing the smooth AG glass comprises: providing glass, a nano-scale anti-glare coating and a fluorine-containing mixture, spraying a portion of the anti-glare coating on the glass surface at an atomizing pressure of 1.1-1.3 Kg / cm2 to form a first spray coating, then spraying another portion of the anti-glare coating on the first spray coating at an atomizing pressure of 1.4-1.6 Kg / cm2 to form a second spray coating, and after curing, spraying the fluorine-containing mixture on the second spray coating to obtain smooth AG glass; it also fails to solve the above technical problems. Summary of the Invention
[0005] The technical problem to be solved by the present invention is to provide an anti-flash point anti-glare glass and a preparation method thereof, so as to solve the flash point problem of the anti-glare glass in the application scenario of high pixel density OLED screen.
[0006] In order to solve the above technical problems, the technical solution adopted by the present invention is: an anti-flash point anti-glare glass, comprising: AG glass, optical glue and LCD or OLED light-emitting module arranged in sequence; the AG glass includes a base layer, and an anti-flash point structural layer is provided on the side of the base layer in contact with the optical glue, and an AG structural layer is provided on the other side of the base layer.
[0007] The anti-flash point structural layer is arranged on the surface of the glass or on the surface of the film layer coated on the glass.
[0008] The refractive index of the anti-flash point structural layer is 1.4 to 2.5; the anti-flash point structural layer contains a plurality of periodic, quasi-periodic or non-periodic holes or protrusions, and its surface shape is plane, spherical or aspherical.
[0009] When the surface shape of the anti-flash point structural layer is a deformed aspherical layer, the description formula is:
[0010]
[0011] Where cx and kx are the curvature and quadratic constant in the x-direction, cy and ky are the curvature and quadratic constant in the y-direction, A is the symmetry coefficient, B is the asymmetry coefficient, and n is the order.
[0012] The anti-flash point structure is a concave hole or a convex hole, and the surface shape is a plane surface shape, a spherical surface shape, a sinusoidal surface shape or a free-curved surface shape. The surface structure size of the concave hole or the convex hole is 1um to 50um; the depth or height of the concave hole or the convex hole is: 0.5um to 10um.
[0013] The method for preparing the anti-flash point anti-glare glass comprises the following steps: 1) treating the glass substrate; 2) coating the film layer; 3) applying photoresist; 4) exposing the film layer; 5) developing the film layer; 6) etching the film layer; and 7) etching the glass.
[0014] 8) Stripping the photoresist and film layer; 9) Polishing.
[0015] In the above step 1), deionized water is first used for preliminary rinsing, and dust and organic impurities on the surface of the substrate are removed by soft brush or ultrasonic means; low-concentration cleaning agent or solvent is added for degreasing and deoiling, and the treatment temperature range is 20-100°C and the treatment time is 1-10 minutes; in the above step 2), vacuum coating or evaporation technology, including physical vapor deposition, chemical vapor deposition, and sputtering coating, is used to coat the glass surface as a barrier layer, and the film layer materials include Cr, Mo, SiO2 and Si3N4; the thickness of the film layer is controlled at within the range.
[0016] In step 3) above, a positive or negative photoresist with a thickness of 0.5-20 μm is coated on the surface of the barrier layer using a slit coating method; the coating speed is controlled between 10-200 mm / s; the gap is maintained in the range of 50-300 μm during the coating process, and the spray pressure is controlled in the range of 0.03-0.98 MPa; after coating, a soft bake is performed to remove the solvent in the photoresist; the soft bake temperature is controlled at 50-200°C for 30-300 seconds; after coating, the thickness and uniformity of the photoresist are tested using a film thickness tester or an optical microscope.
[0017] In step 4), contact, proximity or projection exposure machines are selected based on the batch size and resolution requirements; the exposure energy is between 50 and 500 mJ / cm 2 The specific value is determined by the photoresist characteristics, light source wavelength and resolution level; UV wavelengths include i-line, h-line and g-line, and the wavelength selection is determined by the specific application requirements and the photosensitivity matching of the photoresist; if multi-layer exposure is required, the alignment error is controlled within ±0.5~1μm through the double-sided alignment system; in the above step 5), a specific concentration of developer is used during development, the development time is 30~90s, and a constant temperature is maintained in the range of 20~30℃; in the above step 6), the film layer Before etching, the photoresist pattern is cured: thermal curing or UV curing is performed in the temperature range of 50-500°C for 1-60 minutes. After the pattern is cured, the film layer is etched. Different types of film layers are treated with corresponding etching solutions: for Cr and Mo film layers, a mixed solution of nitric acid or hydrochloric acid is used with a concentration controlled between 1-10%; for SiO2 film layers, hydrofluoric acid is used with a concentration of 5-20%; and for Si3N4 film layers, phosphoric acid is used with a concentration range of 10-30%.
[0018] In the above step 7), hydrofluoric acid of a specific concentration is used as an etchant, and an organic or inorganic acid such as hydrochloric acid or nitric acid is added as an auxiliary component to etch the silicate structure, and the temperature is controlled at 20-50°C to form an etched morphology; in the above step 8), a photoresist removal technology is used to remove the residual photoresist; then, a specific etching solution is used to remove the residual film layer; in the above step 9), hydrofluoric acid of a specific concentration is used as an etcher, and an organic or inorganic acid such as hydrochloric acid or nitric acid is added as an auxiliary component to further acid-etch the etched morphology formed in the glass etching process to form the final AG structure layer and anti-flash point structure layer morphology, and the temperature is controlled at 20-50°C.
[0019] One of the above technical solutions has the following advantages or beneficial effects, which solves the flash point problem of anti-glare glass in the application scenario of high pixel density OLED screen. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 This is a schematic structural diagram of the anti-flash point anti-glare glass provided in an embodiment of the present invention;
[0021] Figure 2 for Figure 1 Schematic diagram of the structure of anti-flash point anti-glare glass;
[0022] The marks in the above figure are: 1, AG glass, 11, base layer, 12, AG structural layer, 13, anti-flash point structural layer, 2, optical adhesive, 3, LCD or OLED light-emitting module DETAILED DESCRIPTION
[0023] The following will clearly and completely describe the technical solutions in the embodiments of the present invention in conjunction with the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative efforts are within the scope of protection of the present invention.
[0024] Example 1
[0025] See also Figures 1-2 This anti-flashing and anti-glare glass comprises: AG glass, optical adhesive, and an LCD or OLED light-emitting module, arranged in sequence. The AG glass includes a base layer, an anti-flashing structural layer on the side of the base layer that contacts the optical adhesive, and an AG structural layer on the other side of the base layer. When used in high-pixel-density LCD or OLED modules, the AG glass can prevent glare while reducing screen flash, thereby eliminating the discomfort caused by flash when viewing the screen.
[0026] The anti-flash point structural layer is arranged on the surface of the glass or on the surface of the film layer coated on the glass.
[0027] The refractive index of the anti-flash point structural layer is 1.4 to 2.5; the anti-flash point structural layer contains a plurality of periodic, quasi-periodic or non-periodic holes or protrusions, and its surface shape is plane, spherical or aspherical.
[0028] When the surface shape of the anti-flash point structural layer is a deformed aspherical layer, its description formula is:
[0029]
[0030] Where cx and kx are the curvature and quadratic constant in the x-direction, cy and ky are the curvature and quadratic constant in the y-direction, A is the symmetry coefficient, B is the asymmetry coefficient, and n is the order.
[0031] The anti-flash point structure is a concave hole or a convex hole, and the surface shape is a plane surface shape, a spherical surface shape, a sinusoidal surface shape or a free-form surface shape. The surface structure size of the concave hole or the convex hole is 1um to 50um; the depth or height of the concave hole or the convex hole is: 0.5um to 10um.
[0032] The method for preparing the anti-flash point anti-glare glass comprises the following steps: 1) treating the glass substrate; 2) coating the film layer; 3) applying photoresist; 4) exposing the film layer; 5) developing the film layer; 6) etching the film layer; and 7) etching the glass.
[0033] 8) Stripping the photoresist and film layer; 9) Polishing.
[0034] In the above step 1), deionized water is first used for preliminary rinsing, and dust and organic impurities on the surface of the substrate are removed by soft brush or ultrasonic means; low-concentration cleaning agent or solvent is added for degreasing and deoiling, and the treatment temperature range is 20-100°C and the treatment time is 1-10 minutes; in the above step 2), vacuum coating or evaporation technology, including physical vapor deposition, chemical vapor deposition, and sputtering coating, is used to coat the glass surface as a barrier layer, and the film layer materials include Cr, Mo, SiO2 and Si3N4; the thickness of the film layer is controlled at The specific value depends on the subsequent etching process conditions and the required aspect ratio of the microstructure. Although a film layer that is too thick can provide better protection, it also increases the etching difficulty and material cost. A film layer that is too thin may be damaged during the etching process, affecting the integrity of the microstructure.
[0035] In step 3), a positive or negative photoresist with a thickness of 0.5-20 μm is applied to the barrier layer using a slot-type coating process. To ensure uniformity of the barrier layer, the coating speed is controlled between 10-200 mm / s, the gap between 50 and 300 μm is maintained during the coating process, and the spray pressure is controlled within the range of 0.03-0.98 MPa. After coating, a soft bake is performed. To better remove solvent from the photoresist and improve its adhesion and stability, the soft bake temperature is controlled at 50-200°C for 30-300 seconds. After coating, the photoresist thickness and uniformity are measured using a film thickness tester or optical microscope.
[0036] In step 4), contact, proximity or projection exposure machines are selected based on the batch size and resolution requirements; the exposure energy is between 50 and 500 mJ / cm 2The specific value is determined by the photoresist characteristics, light source wavelength and resolution level; UV wavelengths include i-line, h-line, and g-line, and the wavelength selection is determined by the specific application requirements and the photosensitivity matching of the photoresist; if multi-layer exposure is required, the alignment error is controlled within ±0.5~1μm through a double-sided alignment system; in the above step 5), a developer of a specific concentration is used during development. In order to obtain a stable development rate and reliable pattern authenticity, the development time is controlled within 30~90s and a constant temperature is maintained in the range of 20~30℃. In the above step 6), the photoresist pattern is cured before the film layer is etched. In order to enhance the corrosion resistance and mechanical strength of the photoresist pattern and prevent deformation or debonding during the etching process, the temperature of the thermal curing or UV curing process is controlled within the temperature range of 50~500℃ and the duration is controlled within 1~60min. After the pattern is solidified, the film layer is etched. Different types of film layers are treated with corresponding etching solutions: for Cr and Mo film layers, a mixed solution of nitric acid or hydrochloric acid is used with a concentration controlled between 1-10%; for SiO2 film layers, hydrofluoric acid is used with a concentration of 5-20%; and for Si3N4 film layers, phosphoric acid is used with a concentration range of 10-30%. The specific concentration depends on the film thickness, moment depth, and sidewall accuracy.
[0037] In the above step 7), hydrofluoric acid of a specific concentration is used as an etchant, and an organic or inorganic acid such as hydrochloric acid or nitric acid is added as an auxiliary component to etch the silicate structure, and the temperature is controlled at 20-50°C to form an etched morphology; in the above step 8), a photoresist removal technology is used to remove the residual photoresist; then, a specific etching solution is used to remove the residual film layer; in the above step 9), hydrofluoric acid of a specific concentration is used as an etcher, and an organic or inorganic acid such as hydrochloric acid or nitric acid is added as an auxiliary component to further acid-etch the etched morphology formed in the glass etching process to form the final AG structure layer and anti-flash point structure layer morphology, and the temperature is controlled at 20-50°C to ensure the stability of the moment process and the etching rate.
[0038] The anti-flash point AG glass is composed of an AG structural layer on the front and an anti-flash point structural layer on the back; the anti-flash point structure is placed on the back glass of the AG structural layer or on the back film layer of the AG structural layer; the refractive index of the surface material where the anti-flash point structure is located is: 1.4 to 2.5; the anti-flash point structural layer is composed of a periodic, quasi-periodic or non-periodic structure; the anti-flash point structure size is 1um to 50um; the anti-flash point structure shape is a concave hole or a convex hole; the anti-flash point structure is close to the AG structural layer (concave hole) or away from the AG structural layer (convex hole) The surface type is a plane surface type, a spherical surface type, a sinusoidal surface type or a free-form surface type; the depth or height of the anti-flash point structure is controlled within the range of 0.5um to 10um. The selection of structural size and height is related to the substrate thickness and the pixel arrangement of the light-emitting module. Within this range, it can better achieve the anti-flash point effect.
[0039] After adopting the above solution, the flash point problem of anti-glare glass in high pixel density OLED screen application scenarios is solved.
[0040] Example 2
[0041] Disclosed is an anti-flash point AG glass comprising: a base layer; an AG structural layer, the AG structural layer being arranged on a surface on a side away from the base layer; and an anti-flash point structural layer, the anti-flash point structural layer being arranged on a surface on a side of the glass base away from the AG structural layer, the anti-flash point structural layer comprising a plurality of holes or protrusions.
[0042] Figure 1 A schematic diagram of an anti-flash AG glass and optical device is shown. Reference 1 in the figure indicates the anti-flash AG glass, which consists of a glass substrate, an upper AG structural surface, and a lower anti-flash structural layer. Reference 2 indicates optical adhesive (OCA), which bonds the anti-flash AG glass to an LCD or OLED light-emitting module. Reference 3 indicates the LCD or OLED light-emitting module.
[0043] By providing the base layer 11, the base layer provides a foundation for the AG structural layer 12 and the anti-flash point structural layer 13, which is beneficial for improving the reliability of the AG structural layer and the anti-flash point structural layer, while ensuring the overall structural stability of the anti-flash point AG glass. By properly designing the arrangement, shape, and height of the AG structural layer, it can achieve an anti-glare function; by properly designing the shape, size, and arrangement of the multiple concave holes or protrusions on the anti-flash point structural layer, it can achieve an anti-flash point function, thereby eliminating the discomfort caused by flash points when the human eye views the display screen.
[0044] Figure 2Schematic diagram of the anti-flash structure layer. The anti-flash structure is placed on the back glass surface of the AG structure layer or on the surface of the film layer coated on the back glass of the AG structure layer. The refractive index of the surface material where the anti-flash structure is located is: 1.4 to 2.5. The anti-flash structure layer contains multiple periodic, quasi-periodic or non-periodic holes or protrusions, and its surface shape is plane, spherical or aspherical. For example Figure 2 The surface shape given in is a deformed aspheric surface, and its description formula is:
[0045]
[0046] Among them, c x and k x are the curvature in the x direction and the quadratic curve constant respectively; c y and k y are the curvature in the y direction and the quadratic curve constant respectively; A is the symmetry coefficient, B is the asymmetry coefficient, and n is the order.
[0047] The surface structure size ranges from 1 μm to 50 μm. The surface shape of the anti-flash point structure on the side close to the AG structure layer (concave hole) or the side away from the AG structure layer (convex) can be flat, spherical, sinusoidal, or free-form. The depth or height of the anti-flash point structure ranges from 0.5 μm to 10 μm.
[0048] The AG structural layer and the anti-flash point structural layer are prepared using similar processes. The main production processes are as follows:
[0049] The first process: glass substrate processing
[0050] First, perform a preliminary rinse with deionized water. Use a soft brush or ultrasonic method to remove dust and organic impurities from the substrate surface. If necessary, add a low-concentration detergent or solvent for degreasing and deoiling. The treatment temperature range is 20-100°C, and the treatment time is 1-10 minutes.
[0051] The second process: coating layer
[0052] Using vacuum coating or evaporation technology, such as physical vapor deposition (PVD), chemical vapor deposition (CVD), sputtering coating, etc., the coating layer on the glass surface is used as a barrier layer. The film material can be selected from Cr (chromium), Mo (molybdenum), SiO2 (silicon dioxide) and Si3N4 (silicon nitride). The thickness of the film layer is usually controlled at within the range.
[0053] The third step: coating photoresist
[0054] Slit coating is used to coat positive or negative photoresist with a thickness of 0.5-20μm on the surface of the barrier layer. The coating speed is usually controlled between 10-200mm / s to ensure uniform coverage. During the coating process, the GAP (gap between the adhesive layer and the substrate) is maintained in the range of 50-300μm, and the spray pressure is controlled in the range of 0.03-0.98MPa. After coating is completed, soft baking is usually required to remove the solvent in the photoresist and improve the adhesion and stability of the photoresist. The soft baking temperature is generally controlled at 50-200℃ and the time is 30-300 seconds. After coating is completed, the thickness and uniformity of the photoresist can be tested by means of a film thickness tester or optical microscope to ensure that it meets the requirements of subsequent photolithography processes.
[0055] The fourth step: exposure
[0056] Contact, proximity or projection exposure machines are selected based on batch and resolution requirements. Exposure energy is usually between 50 and 500 mJ / cm 2 The specific value is determined by the photoresist characteristics, light source wavelength, and resolution level. Commonly used UV wavelengths are i-line (365nm), h-line (405nm), and g-line (436nm). Choosing the appropriate wavelength should be determined based on the specific application requirements and the photosensitivity of the photoresist. If multi-layer exposure is required, a double-sided alignment system is used to control the alignment error within ±0.5-1μm, ensuring precise matching of the multi-layer pattern.
[0057] The fifth process: development
[0058] During development, a developer of a specific concentration (such as TMAH tetramethylammonium hydroxide or potassium hydroxide KOH solution) is used. The development time is generally around 30 to 90 seconds, and a constant temperature is maintained in the range of 20 to 30°C to obtain a stable development rate and reliable pattern authenticity.
[0059] The sixth process: film etching
[0060] Before etching the film, the photoresist pattern typically needs to be cured. Specifically, thermal or UV curing can be performed at temperatures between 50°C and 500°C for 1 to 60 minutes to enhance the corrosion resistance and mechanical strength of the photoresist pattern and prevent deformation or debonding during the etching process. Only after the pattern is cured can the film be etched.
[0061] Different types of film layers are treated with corresponding etching solutions: for Cr and Mo film layers, a mixed solution of nitric acid or hydrochloric acid is mainly used, with the concentration controlled between 1-10%; for SiO2 film layers, hydrofluoric acid is used, with its concentration usually between 5-20%; and for Si3N4 film layers, phosphoric acid is used, with a concentration range of 10-30%.
[0062] The seventh process: glass etching
[0063] A certain concentration of HF (hydrofluoric acid) is used as the main etching machine. Organic or inorganic acids such as hydrochloric acid and nitric acid can be added as auxiliary components to etch the silicate structure (mainly SiO2). The temperature is generally controlled at 20-50°C to form an etching morphology of a certain depth.
[0064] The eighth process: stripping the photoresist and film layer
[0065] Photoresist removal technology is used to remove the remaining photoresist. After that, a specific etching solution is used to remove the remaining film layer.
[0066] Ninth process: polishing
[0067] A certain concentration of HF (hydrofluoric acid) is used as the main etching machine. Organic or inorganic acids such as hydrochloric acid and nitric acid can be added as auxiliary components to further acid-etch the etching morphology formed in the glass etching process to form the final AG structure layer and anti-flash point structure layer morphology. The temperature is generally controlled at 20-50°C.
[0068] Note: The preparation of the AG structural layer and the anti-flash point structural layer is carried out in sequence. After the preparation of the AG structural layer is completed, it must be protected by an acid-proof film to prevent it from being damaged in the subsequent preparation process of the anti-flash point structural layer.
[0069] The anti-flash point AG glass is composed of an AG structural layer on the front and an anti-flash point structural layer on the back; the anti-flash point structure is placed on the back glass of the AG structural layer or on the back film layer of the AG structural layer; the refractive index of the surface material where the anti-flash point structure is located is: 1.4~2.5; the anti-flash point structural layer is composed of a periodic, quasi-periodic or non-periodic structure; the size of the anti-flash point structure is 1um~50um; the shape of the anti-flash point structure is a concave hole or a convex hole; the surface type of the anti-flash point structure close to the AG structural layer (concave hole) or away from the AG structural layer (convex hole) is a plane surface type, a spherical surface type, a sinusoidal surface type or a free-form surface type; the depth or height of the anti-flash point structure is: 0.5um~10um.
[0070] After adopting the above solution, the AG glass used in high-pixel-density LCD or OLED modules can not only play an anti-glare function but also reduce the generation of screen flash points, thereby eliminating the discomfort caused by flash points when the human eye views the screen.
[0071] In the description of the present invention, it should be understood that the terms "coaxial", "bottom", "one end", "top", "middle", "the other end", "upper", "one side", "top", "inside", "front", "center", "both ends", etc., indicating the orientation or position relationship, are based on the orientation or position relationship shown in the accompanying drawings, and are only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as a limitation on the present invention.
[0072] In the present invention, unless otherwise clearly stipulated and limited, the terms "install", "set", "connect", "fix", "screw" and the like should be understood in a broad sense. For example, it can be a fixed connection, a detachable connection, or an integrated connection; it can be a mechanical connection or an electrical connection; it can be a direct connection or an indirect connection through an intermediate medium; it can be the internal connection of two elements or the interaction relationship between two elements. Unless otherwise clearly defined, ordinary technicians in this field can understand the specific meanings of the above terms in the present invention according to the specific circumstances.
[0073] While embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions, and variations may be made to these embodiments without departing from the principles and spirit of the invention, and that the scope of the invention is defined by the appended claims and their equivalents.
Claims
1. An anti-flash point anti-glare glass, characterized in that: The invention comprises: AG glass, optical glue and LCD or OLED light-emitting module arranged in sequence; the AG glass comprises a base layer, an anti-flash point structural layer is provided on the side of the base layer in contact with the optical glue, and an AG structural layer is provided on the other side of the base layer.
2. The anti-flash point anti-glare glass according to claim 1, characterized in that: The anti-flash point structural layer is arranged on the surface of the glass or on the surface of the film layer coated on the glass.
3. The anti-flash point anti-glare glass according to claim 2, characterized in that: The refractive index of the anti-flash point structural layer is 1.4 to 2.5; the anti-flash point structural layer contains a plurality of periodic, quasi-periodic or non-periodic holes or protrusions, and its surface shape is plane, spherical or aspherical.
4. The anti-flash point anti-glare glass according to claim 3, characterized in that: When the surface shape of the anti-flash point structural layer is a deformed aspherical layer, the description formula is: Where cx and kx are the curvature and quadratic constant in the x-direction, cy and ky are the curvature and quadratic constant in the y-direction, A is the symmetry coefficient, B is the asymmetry coefficient, and n is the order.
5. The anti-flash point anti-glare glass according to claim 4, characterized in that: The anti-flash point structure is a concave hole or a convex hole, and the surface shape is a plane surface shape, a spherical surface shape, a sinusoidal surface shape or a free-curved surface shape. The surface structure size of the concave hole or the convex hole is 1um to 50um; the depth or height of the concave hole or the convex hole is: 0.5um to 10um.
6. The method for preparing the anti-flash point anti-glare glass according to claim 5, wherein: The process includes the following steps: 1) processing the glass substrate; 2) coating the film; 3) applying photoresist; 4) exposing the film; 5) developing the film; 6) etching the film; and 7) etching the glass. 8) Stripping the photoresist and film layer; 9) Polishing.
7. The method for preparing the anti-flash point anti-glare glass according to claim 6, wherein: In the above step 1), deionized water is first used for preliminary rinsing, and dust and organic impurities on the surface of the substrate are removed by soft brush or ultrasonic means; low-concentration cleaning agent or solvent is added for degreasing and deoiling, and the treatment temperature range is 20-100°C and the treatment time is 1-10 minutes; in the above step 2), vacuum coating or evaporation technology, including physical vapor deposition, chemical vapor deposition, and sputtering coating, is used to coat the glass surface as a barrier layer, and the film layer materials include Cr, Mo, SiO2 and Si3N4; the thickness of the film layer is controlled at within the range.
8. The method for preparing the anti-flash point anti-glare glass according to claim 7, wherein: In step 3) above, a positive or negative photoresist having a thickness of 0.5-20 μm is applied to the barrier layer surface by slot coating; the coating speed is controlled between 10-200 mm / s; the gap is maintained in the range of 50-300 μm during the coating process, and the spray pressure is controlled within the range of 0.03-0.98 MPa; after coating, a soft bake is performed to remove the solvent from the photoresist; the soft bake temperature is controlled at 50-200° C. for 30-300 seconds; After coating is completed, the thickness and uniformity of the photoresist are tested using a film thickness tester or optical microscope.
9. The method for preparing the anti-flash point anti-glare glass according to claim 8, wherein: In step 4), contact, proximity or projection exposure machines are selected based on the batch size and resolution requirements; the exposure energy is between 50 and 500 mJ / cm 2 The specific value is determined by the photoresist characteristics, light source wavelength and resolution level; UV wavelengths include i-line, h-line and g-line. The wavelength selection is determined by the specific application requirements and the photosensitivity matching of the photoresist. If multi-layer exposure is required, the alignment error is controlled within ±0.5 to 1 μm through a double-sided alignment system; in the above step 5), a developer of a specific concentration is used during development, the development time is 30 to 90 seconds, and a constant temperature is maintained in the range of 20 to 30°C; in the above step 6), the photoresist pattern is cured before the film layer is etched: thermal curing or UV curing is performed in the temperature range of 50 to 500°C for 1 to 60 minutes. After the pattern is cured, the film layer is etched; for different types of film layers, corresponding etching solutions are used for treatment: for Cr and Mo film layers, a mixed solution of nitric acid or hydrochloric acid is used, and the concentration is controlled between 1-10%; for SiO2 film layers, hydrofluoric acid is used, and its concentration is 5-20%; and for Si3N4 film layers, phosphoric acid is used, and the concentration range is 10-30%.
10. The method for preparing the anti-flash point anti-glare glass according to claim 9, wherein: In step 7), a specific concentration of hydrofluoric acid is used as an etchant, and an organic or inorganic acid such as hydrochloric acid or nitric acid is added as an auxiliary component to etch the silicate structure at a temperature of 20-50° C. to form an etched morphology. In step 8), a photoresist removal technique is used to remove the residual photoresist. Thereafter, a specific etching solution is used to remove the residual film layer. In the above step 9), a hydrofluoric acid of a specific concentration is used as an etching machine, and an organic or inorganic acid such as hydrochloric acid or nitric acid is added as an auxiliary component to further acid-etch the etched morphology formed in the glass etching process to form the final AG structure layer and anti-flash point structure layer morphology, and the temperature is controlled at 20-50°C.
Citation Information
Patent Citations
Preparation method of smooth AG glass and the smooth AG glass
CN110615622A